2011
DOI: 10.5530/pj.2011.24.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro anthelminthic activity of Leucas aspera extracts

Abstract: Helminths infections are also among the most common infections in human, affecting a large proportion of the world's population in developing countries and produce a global burden of disease. Pherithema posthuma a helminthes is commonly known as earth-worms, Leucas aspera herb is distributed throughout India. the anthelminthic property of Leucas aspera was evaluated using Pherithema posthuma as an experimental model. Piperazine citrate was used as the standard reference. earthworm belonging to control group sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Among the various test concentrations, ethanol extract 250 mg/ml showed significant anthelmintic activity with death time of 46.33 min as compared to the standard drug at 50 mg/ml that showed paralysis at 31.33 min and death time as 40.67 min. The investigation thus revealed that ethanol extract of C. roseus showed significant antihelmintic activity against Pheretima posthuma supporting the ethnomedical claims of C. roseus as an antihelmintic plant 57 .…”
Section: Antioxidant Potentialsupporting
confidence: 59%
“…Among the various test concentrations, ethanol extract 250 mg/ml showed significant anthelmintic activity with death time of 46.33 min as compared to the standard drug at 50 mg/ml that showed paralysis at 31.33 min and death time as 40.67 min. The investigation thus revealed that ethanol extract of C. roseus showed significant antihelmintic activity against Pheretima posthuma supporting the ethnomedical claims of C. roseus as an antihelmintic plant 57 .…”
Section: Antioxidant Potentialsupporting
confidence: 59%
“…e method adopted was as described in literature with modifications [6,16]. Eight groups of test agents were administered to twenty two groups of adult earthworms, with each group containing three earthworms of approximately equal size.…”
Section: In Vitro Anthelminthic Effects Of Crude Extractsmentioning
confidence: 99%
“…Over the years, conventional anthelminthic drugs, such as, albendazole, mebendazole, ivermectin, piperazine, and niclosamide, have been widely patronized to treat helminth infections, in both livestock and humans. However, due to factors such as cost of these medicines [6], their toxic effects [7], and reported cases of resistance development [5], their patronage and usefulness especially among people living in low-middle income countries have been limited and substituted with cheaper alternatives, mainly, herbal medicines [7]. Several studies have documented the traditional or folkloric use of herbal medicines for helminthiases [1,4,8], and scientific justifications have been widely documented for some of these medicinal plants [2,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For the experiment Pheretima posthuma was taken as model. Through several experimental studies 250 mg/ml concentration of ethanol extract is effective in helminthic disease [19].…”
Section: Anti-helminthic Activitymentioning
confidence: 99%